In vitro susceptibility of respiratory isolates of streptococcus pneumoniae and streptococcus pyogenes to telithromycin and 11 other antimicrobial agents: Turkish results of E-Baskett-II Surveillance Study - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2007)
In respiratory tract infections, therapy is often empirical and there is a need for local data on the rate of resistance to available antimicrobials. In this multicentre study which is a part of the international e-BASKETT-II surveillance study, respiratory isolates of Streptococcus pneumoniae (n=260) and Streptococcus pyogenes (n=312) collected between September 2002 and June 2003 from 18 hospitals in Turkey were tested against penicillin G, amoxicillin, cefuroxime, ceftriaxone, erythromycin, clarithromycin, azithromycin, clindamycin, telithromycin, tetracycline, levofloxacin and vancomycin. Antibiotic susceptibilities were determined with disk diffusion method and confirmed with broth dilution method following the CLSI guidelines. Isolates which were resistant to erythromycin were genotyped by polymerase chain reaction. In S.pneumoniae 11.5% of the isolates were highly and 22.7% were intermediately resistant to penicillin. Rate of resistance to erythromycin, clarithromycin, azithromycin was 17.3%, and 21.5% of the isolates were resistant to tetracycline. Resistance to levofloxacin and vancomycin was not observed and only one isolate was found intermediately resistant (MIC=2 mu g/mL) to telithromycin. Genotypes in erythromycin-resistant isolates were ermB (77.8%), mefA (17.8%) and ermB+mefA (2.2%). S.pyogenes isolates were uniformly susceptible to beta-lactams and vancomycin, and only one isolate was intermediately resistant to levofloxacin. Macrolide resistance was observed in 1.3% of the isolates and three out of these harboured the mefA gene. One isolate with an MIC of 4 mu g/mL for telithromycin had ermB gene. Telithromycin has demonstrated a good in vitro activity against macrolide-resistant respiratory tract isolates. As a result, e-BASKETT-II surveillance study has been one of the most extensive in vitro studies comparing telithromycin to available antimicrobial agents for respiratory tract infections in Turkey.
Keywords: respiratory isolates; antimicrobial resistance; telithromycin; Streptococcus pneumoniae; Streptococcus pyogenes; GROUP-A STREPTOCOCCI; MACROLIDE RESISTANCE; HAEMOPHILUS-INFLUENZAE; MORAXELLA-CATARRHALIS; TRACT INFECTIONS; PENICILLIN RESISTANCE; TURKEY; KETOLIDE; ANTIBACTERIAL; MULTICENTER